2009
DOI: 10.3109/00016480903311252
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear pathology in human temporal bones with otitis media

Abstract: Conclusion-Middle and inner ear interactions in otitis media can lead to cochlear pathology. More severe pathological changes observed in the basal turn of the cochlea are consistent with prevalence of sensorineural hearing loss at higher frequencies in patients with otitis media.Methods-Of 614 temporal bones with otitis media, 47 with chronic and 35 with purulent otitis media were selected following strict exclusion of subjects with a history of acoustic trauma, head trauma, ototoxic drugs, and other diseases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
44
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 15 publications
4
44
0
Order By: Relevance
“…A significant loss of outer and inner hair cells, as well as significant atrophy of the stria vascularis in the basal turn of the cochlea, has been observed in CSOM patients. The basal turn of the cochlea also demonstrated severe pathological changes that were consistent with the high-frequency SNHL in CSOM patients (Cureoglu et al, 2004;Joglekar et al, 2010). SNHL in CSOM patients is often demonstrated by higher bone conduction (BC) thresholds in the audiogram.…”
Section: Hearing Lossmentioning
confidence: 71%
See 1 more Smart Citation
“…A significant loss of outer and inner hair cells, as well as significant atrophy of the stria vascularis in the basal turn of the cochlea, has been observed in CSOM patients. The basal turn of the cochlea also demonstrated severe pathological changes that were consistent with the high-frequency SNHL in CSOM patients (Cureoglu et al, 2004;Joglekar et al, 2010). SNHL in CSOM patients is often demonstrated by higher bone conduction (BC) thresholds in the audiogram.…”
Section: Hearing Lossmentioning
confidence: 71%
“…The majority of SNHL in CSOM patients is in the high-frequency range and is unilateral (Jensen et al, 2013). A recent study has also shown that bacterial toxins found in the middle ear during CSOM can pass into the cochlea and result in cochlear pathology (Joglekar et al, 2010). These bacterial toxins can be exotoxins (proteins) produced by both Gram-positive and Gramnegative bacteria, or endotoxins (LPSs of the outer membrane of Gram-negative bacteria).…”
Section: Hearing Lossmentioning
confidence: 99%
“…This idea was supported by the histological experiments of temporal bones. Joglekar et al [1] showed 19% labyrinthine inflammatory changes in temporal bones with COM. Meyerhoff et al [18] reviewed 123 temporal bones with COM accompanied by labyrinthitis.…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by histological studies. [1] We evaluated tinnitus symptoms of participants before and after middle ear surgery. Although it was not a primary complaint, 35 patients had a complaint of tinnitus and this symptom completely disappeared in 15 of 35 patients following surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation